2019
DOI: 10.3389/fmats.2019.00148
|View full text |Cite
|
Sign up to set email alerts
|

Fluoride-Sulfophosphate/Silica Hybrid Fiber as a Platform for Optically Active Materials

Abstract: Pressure-assisted melt filling (PAMF) of prefabricated micro-capillaries has been proven an effective way of fabricating hybrid optical fiber (HOF) from unusual combinations of materials. Here, we extend the applicability of PAMF to multi-anionic fluoride-sulfophosphate (FPS) glasses. FPS glasses provide extended transmission windows and high solubility for various transition metal (TM) and rare earth (RE) ion species. Using PAMF for fabricating FPS/silica HOFs can therefore act as a platform for a broad varie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 46 publications
0
4
0
Order By: Relevance
“…Multimaterial or hybrid optical fibers now represent a fast‐growing subfield within fiber optics and are, unquestionably, amongst the most exciting from both a materials perspective and from a performance and application aspect. The field is too large to fully survey though the interested reader is directed to the reviews noted previously 50,246,247 . Here important advancements include new combinations of fiber materials and fabrication processes, 247‐250 integration of electrodes, 251 and other in‐fiber structures 252‐254 generally not possible in conventional glass systems.…”
Section: Areas For Continued Study and Developmentmentioning
confidence: 99%
See 1 more Smart Citation
“…Multimaterial or hybrid optical fibers now represent a fast‐growing subfield within fiber optics and are, unquestionably, amongst the most exciting from both a materials perspective and from a performance and application aspect. The field is too large to fully survey though the interested reader is directed to the reviews noted previously 50,246,247 . Here important advancements include new combinations of fiber materials and fabrication processes, 247‐250 integration of electrodes, 251 and other in‐fiber structures 252‐254 generally not possible in conventional glass systems.…”
Section: Areas For Continued Study and Developmentmentioning
confidence: 99%
“…The field is too large to fully survey though the interested reader is directed to the reviews noted previously. 50,246,247 Here important advancements include new combinations of fiber materials and fabrication processes, [247][248][249][250] integration of electrodes, 251 and other in-fiber structures [252][253][254] generally not possible in conventional glass systems.…”
mentioning
confidence: 99%
“…Transition metal ions with their weakly bound d electrons (such as V 5+ , Ti 4+ , Cu + , Mn 2+ , Cr 4+ , Co 2+ , Ni 2+ , and Ag + ), [13][14][15][16][17][18][19][20][21] main group metal ions (such as Pb + , Sn 2+ , Bi 3+ , Te 4+ , and Sb 3+ ), [22][23][24][25][26][27][28] quantum dots (such as PbS 29 ), and structural defects (such as oxygen vacancies 30 ) present such alternatives. Among these, bismuth (Bi) ions are of particular interest due to their large variability in terms of the oxidation state that can be stabilized in glass matrices.…”
Section: Introductionmentioning
confidence: 99%
“…For example, it has been found that the glass-forming ability and corrosion resistance of phosphate glasses can be enhanced significantly through the introduction of sulfate anions (SO 4 2– ), even though the glass structure was increasingly depolymerized when replacing P 2 O 5 by SO 3 . Similar relationships between glass structure and variations in anion content are of interest for understanding the properties of optically active ions doped into such materials, whereby the variation of anion species offers a range of new ligand configurations as compared to that of conventional phosphate glasses. , Furthermore, anion exchange may reduce the phonon energy such as in the prominent fluoride-phosphate (FP) glasses , and may also enhance the transmission window toward the deep blue or ultraviolet (UV) spectral range. , …”
Section: Introductionmentioning
confidence: 99%